Without a compass: Salonikan Jews in Nazi Concentration Camps and later - Zezza, Stefania (European Spatial Research and Policy, 2021)
During the Holocaust, the largest Sephardi community in the world located in Saloniki was almost completely destroyed. Despite their limited number in comparison with that of Ashkenazi Jews, the Salonikan Jews, initially deported to Auschwitz Birkenau and Bergen Belsen, went through all the hardest experiences and were sent to many camps in occupied Poland, and in Germany. This article explores, using archival documents and the testimonies, the geographical directions of their deportations. It also analyses historical coordinates and the Salonikan Jews’ characteristics which affected their destinations and the itinerary with which they were forced to cope.